2020
DOI: 10.14569/ijacsa.2020.0110751
|View full text |Cite
|
Sign up to set email alerts
|

Household Overspending Model Amongst B40, M40 and T20 using Classification Algorithm

Abstract: The family economy is a critical indicator of the well-being of a family institution. It can be seen by the total income and how well the household finances is managed. In Malaysia, the household income level is categorized as B40, M40 and T20. These categories can also indicate the poverty level of the household. Overspending is a phenomenon where the monthly expenses are more than the household's total income, which affects economic wellbeing. Finding important factors that affect the spending patterns among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…These items are purchased by the household to meet the requirement, and this spending is referred to as consumption (Yusof et. al., 2019& Othman et al 2020. Domestic purchases, on the other hand, are not all categorised as consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These items are purchased by the household to meet the requirement, and this spending is referred to as consumption (Yusof et. al., 2019& Othman et al 2020. Domestic purchases, on the other hand, are not all categorised as consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Machine learning is a data analysis tool that automates the creation of analysis models. It is an artificial intelligence branch focused on the concept that systems can learn from data, detect patterns, and make choices with minimal human intervention [1][2][3][4]. Machine learning is the most popular and dominant approach to decision making because of the ability to automate complex tasks [3], [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Their research found that poverty analysis is strengthened by examining the relationship between income and deprivation score using the multidimensional poverty indicators. On top of that, Chamboko and Re [ 17 ] have mapped multiple deprivation patterns for 13 areas in Namibia using GIS application and using the K-Means algorithm for clustering purposes. To build scores and thus reduce the number of deprivation dimensions, they applied Principal Component Analysis (PCA).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in unsupervised learning, the data on learning process is unlabeled to view unusual structures or patterns without clear learning goals [9][10][11]. Many studies have been conducted in analyzing multidimensional poverty using machine learning methods such as classification and clustering [12][13][14][15][16][17]. Clustering technique is a method of collecting data objects and grouping them based on the similarity of objects to gain an in-depth understanding of data distribution.…”
Section: Introductionmentioning
confidence: 99%